Anchorage performance of a modified cable anchor subjected to different joint opening conditions. (20th June 2022) - Chen, Jianhang; Liu, Peng; Liu, Lei; Zeng, Banquan; Zhao, Hongbao; Zhang, Cun; Zhang, Junwen; Li, Danqi
Highlights: The influence of the joint opening on the anchorage performance of modified cable anchors was analysed. Experimental tests were conducted under confined and unconfined environment. The pre-peak and post-peak performance of modified cable anchors were compared and analysed. Abstract: In tunnelling engineering, the cable anchor is usually used to reinforce the surrounding rock mass. Site observation shows that the cable anchor may be subjected to different joint opening conditions. However, little study has been launched to study the influence of the joint opening on the anchorage performance of cable anchors. This paper conducted the laboratory Short Encapsulation Pulling Test (SEPT) to study the anchorage performance of a modified cable anchor subjected to different joint opening conditions. During the test, the joint opening was simulated with the bearing plate whose central diameter was different. The results showed that when the joint opening size increases, the maximum load-carrying capacity of cable anchors decreases. This was observed under both unconfined and confined boundary conditions. Moreover, under the confined condition, there was a threshold for the joint opening size. Once the joint opening size was beyond that threshold, further increasing the joint opening size had marginal effect on the capacity of cable anchors. Additionally, under the confined condition, the maximum load-carrying capacity of cable anchors was apparently higher. Furthermore, under the confined condition, cable anchors showed apparent residual load-carrying capacity in the post-failure stage. By contrast, under the unconfined condition, after the peak, the load-carrying capacity of cable anchors dropped dramatically. This leaded to negligible residual load-carrying capacity.